Changed genome heterochromatinization upon prolonged activation of the Raf/ERK signaling pathway. - Catherine Martin; Songbi Chen; Daniela Heilos; Guido Sauer; Jessica Hunt; Alexander George Shaw; Paul Francis George Sims; Dean Andrew Jackson; Josip Lovrić (PLoS ONE)
The Raf/ERK (Extracellular Signal Regulated Kinase) signal transduction pathway controls numerous cellular processes, including growth, differentiation, cellular transformation and senescence. ERK activation is thought to involve complex spatial and temporal regulation, to achieve a high degree of specificity, though precisely how this is achieved remains to be confirmed. We report here that prolonged activation of a conditional form of c-Raf-1 (BXB-ER) leads to profound changes in the level and distribution of a heterochromatic histone mark. In mouse fibroblasts, the heterochromatic trimethylation of lysine 9 in histone H3 (H3K9Me3) is normally confined to pericentromeric regions. However, following ERK activation a genome-wide redistribution of H3K9Me3 correlates with loss of the histone modification from chromocentres and the appearance of numerous punctuate sites throughout the interphase nucleus. These epigenetic changes during interphase correlate with altered chromosome structure during mitosis, where robust H3K9Me3 signals appear within telomeric heterochromatin. This pattern of heterochromatinization is distinct from previously described oncogene induced senescence associated heterochromatin foci (SAHF), which are excluded from telomeres. The H3K9Me3 histone mark is known to bind the major heterochromatin protein HP1 and we show that the alterations in the distribution of this histone epistate correlate with redistribution of HP1β throughout the nucleus. Interestingly while ERK activation is fully reversible, the observed chromatin changes induced by epigenetic modifications are not reversible once established. We describe for the first time a link from prolonged ERK activation to stable changes in genome organization through redistribution of heterochromatic domains involving the telomeres. These epigenetic changes provide a possible mechanism through which prolonged activation of Raf/ERK can lead to growth arrest or the induction of differentiation, senescence and cancer.